Characteristics and influencing factors of early childhood teachers’ work stress and burnout: A comparative study between China, Ghana, and Pakistan - Chen, Siyuan; Ntim, Seth Yeboah; Zhao, Yilun; Qin, Jinliang (Frontiers in Psychology, 2023)
Studies have documented early childhood teachers’ stress and burnout in diverse ways including through situations and characteristics, but few have focused on comparisons among countries, especially developing ones. Meanwhile, as a major force of emotional involvement, the efforts of female teachers, who are more sensitive and tend to provide emotional responses, are often ignored. By using multi-group structural equation modeling, this study investigated the similarities and differences in the characteristics and influencing factors of early childhood teachers’ stress, burnout, and gender, between China, Ghana, and Pakistan. The participants included 945 preschool and lower primary teachers recruited from Zhejiang Province in China, the Ashanti Region in Ghana, and Punjab, Pakistan. The results show that across the three countries, female teachers are more stressed out, with higher emotional demands and work-family conflicts, and are more prone to burnout with a greater level of emotional exhaustion and a lower level of personal accomplishments than male teachers. Chinese teachers are the most stressed-out group with the highest level of burnout. Notably, early childhood teachers in Ghana have the lowest level of emotional demands compared to teachers in China and Pakistan. Teachers in Pakistan are unlikely to experience burnout, with the lowest level of emotional exhaustion and the highest level of personal accomplishments. The possible reasons for the findings and future directions are also discussed.